Retinoic acid catabolizing enzyme CYP26C1 is a genetic modifier in SHOX deficiency - Antonino Montalbano; Lonny Juergensen; Ralph Roeth; Birgit Weiss; Maki Fukami; Susanne Fricke‐Otto; Gerhard Binder; Tsutomu Ogata; Eva Decker; Gudrun Nuernberg; David Hassel; Gudrun A Rappold (EMBO Molecular Medicine)
Abstract Mutations in the homeobox gene SHOX cause SHOX deficiency, a condition with clinical manifestations ranging from short stature without dysmorphic signs to severe mesomelic skeletal dysplasia. In rare cases, individuals with SHOX deficiency are asymptomatic. To elucidate the factors that modify disease severity/penetrance, we studied a three‐generation family with SHOX deficiency. The variant p.Phe508Cys of the retinoic acid catabolizing enzyme CYP26C1 co‐segregated with the SHOX variant p.Val161Ala in the affected individuals, while the SHOX mutant alone was present in asymptomatic individuals. Two further cases with SHOX deficiency and damaging CYP26C1 variants were identified in a cohort of 68 individuals with LWD. The identified CYP26C1 variants affected its catabolic activity, leading to an increased level of retinoic acid. High levels of retinoic acid significantly decrease SHOX expression in human primary chondrocytes and zebrafish embryos. Individual morpholino knockdown of either gene shortens the pectoral fins, whereas depletion of both genes leads to a more severe phenotype. Together, our findings describe CYP26C1 as the first genetic modifier for SHOX deficiency.